2011
DOI: 10.4012/dmj.2010-053
|View full text |Cite
|
Sign up to set email alerts
|

Flexural properties of three kinds of experimental fiber-reinforced composite posts

Abstract: The aim of this study was to estimate the flexural properties of three kinds of experimental fiber-reinforced composite (FRC) posts and to evaluate their potential use as posts. Experimental FRC posts were fabricated with glass, aramid, and UHMWP fibers. Commercial FRC posts were used for comparison. A three-point bending test was performed at a crosshead speed of 1 mm/min. Experimental glass fiber posts showed significantly higher flexural strengths and moduli than aramid and UHMWP posts. Experimental UHMWP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…Aramid fibers have been shown to increase the impact strength of PMMA resin significantly and to enhance the fracture resistance of acrylic resin 10,15,20) . UHMWP fibers are biocompatible and possess a high degree of stiffness, toughness, and strength 11,21,22) . The mechanical properties of FRC are dependent upon the composition of the fiber, fiber orientation, the ratio of fiber to resin, and the adhesion between the fiber and resin matrix 11,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aramid fibers have been shown to increase the impact strength of PMMA resin significantly and to enhance the fracture resistance of acrylic resin 10,15,20) . UHMWP fibers are biocompatible and possess a high degree of stiffness, toughness, and strength 11,21,22) . The mechanical properties of FRC are dependent upon the composition of the fiber, fiber orientation, the ratio of fiber to resin, and the adhesion between the fiber and resin matrix 11,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…UHMWP fibers are biocompatible and possess a high degree of stiffness, toughness, and strength 11,21,22) . The mechanical properties of FRC are dependent upon the composition of the fiber, fiber orientation, the ratio of fiber to resin, and the adhesion between the fiber and resin matrix 11,[23][24][25] . A hybrid FRC is obtained with two or more different types of fibers in a single matrix and has a better combination of properties than composites containing only a single fiber type 10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber post used in the present study showed superior mechanical properties than fiber posts with similar diameters tested in some previous studies [17][18][19] . According to Abdulmajeed et al 17 , increasing fiber volume fraction enhances the mechanical properties of fiber posts.…”
Section: Ereifej N Garcia E Noroña D and Grande Rmentioning
confidence: 59%
“…In contrast, the specimens in the current study that were sectioned with a carbide disk presented a more regular surface, showing that water irrigation may be sufficient to promote a more homogeneous surface and prevent the formation of burnt areas (Burns). Two-point 2) and three-point 16,[20][21][22] flexural strength test have been extensively used to assess the mechanical properties (hardness, tensile, flexural modulus) of fiber reinforced polymeric materials used in dentistry. Therefore, these evaluation methods provide data that can be compared to the data from other studies.…”
Section: Discussionmentioning
confidence: 99%